Mitigation Policy of Flood Disaster in Sungai Penuh Town Province of Jambi, Indonesia - Raflus, Ristika Utami; Iskarni, Paus; Legaya, Nicole (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
This research is based on the weak role of government in reducing the risk of flood disaster in Sungai Penuh Town appropriately, thus efforts are needed to avoid and decrease this situation, in other word mitigation of flood disaster is needed. The purpose of this study are analyzed the characteristics of area based catastrophic flooding, flood hazard, and flood risk and formulate mitigation policy and direction of flood disaster. The type of research is combined or mixed method. This study using quantitative Method used in determining volcano hazard, the level of vulnerability of the community, volcano risk and the use of qualitative Method used in determining the direction and mitigation policies towards mitigation of flood disaster. Findings research shows two characteristics area are good area that didn’t hazard of flood covering 4872 ha and bad area that cause the flood covering 30403 ha, with three levels of flood hazard are high flood hazard covering 3145 ha, medium flood hazard covering 1726 ha, and low flood hazard covering 30403 ha and three levels of flood risk are flood risk high covering 4872 ha, flood risk medium covering 6395 ha, and flood risk low covering 24008 ha. The high flood harmful for environment and agriculture, due this situation, this research is needed mitigation policy of flood disaster which set up zoning on any flood hazard zone, normalization downstream/ estuaries of river, doing and improving the coordination of government in the cross-sectoral of town and regency, developing the early warning system, and socialitation and provide training/ non-agricultural skills to the society.